Efektivitas Air Buah Lontar dalam Mempertahankan Motilitas, Viabilitas dan Daya Tahan Hidup Spermatozoa Sapi Bali - MataHine, Thomas; ., Burhanuddin; Marawali, Aloysius (Jurnal Veteriner, 2014)
The objective of this study was to determine the effectiveness of palmyra juice in maintaining motility,viability, and longevity of bali cattle sperm during in vitro storage. Semen collected from a four year oldbali bull had been trained to serve an artificial vagina. Good quality semen divided into four tubes to betreated with: without extender (negative control), citrate-egg yolk (citrate-EY) and coconut water-egg yolk(CW-EY) as positive control; and palmyra juice-egg yolk (PJ-EY), and then stored in a refrigerator attemperature 3 - 8oC. Each treatment was repeated five times to form 20 experimental units. The resultsshowed that up to the fourth day of storage, sperm preserved in PJ-EY had motility 44%, higher (P<0.05)than citrate-EY, CW-EY, and without extender, i.e 30%, 18%, and 0%, respectively. PJ-EY extender alsoyield sperm viability 60%, higher (P<0.05) than citrate-EY, CW-EY, and without extender i.e 50%, 32% and0%, respectively. Sperm livability achieve 11.20 days in PJ-EY, longer (P <0.05) than citrate-EY, CW-EYand without extender, i.e 9.60 days, 7.60 days , and 1.31 days, respectively. In conclusion that palmyrajuice-egg yolk extender effective to maintain motility, viability, and longevity of bali cattle sperm duringin vitro preservation.
Keywords: palmyra juice, egg yolk, motility, viability, longevity, sperm, bali cattle